1 − 2 + 3 + 4 − 5 + 6 + 7 − 8 + 9 + 1 0 − ⋯ − 2 0 0 0 + 2 0 0 1 + 2 0 0 2 − 2 0 0 3 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Notice that:
1 − 2 + 3 = 2 4 − 5 + 6 = 5 7 − 8 + 9 = 8 … 1 9 9 9 − 2 0 0 0 + 2 0 0 1 = 2 0 0 0
From here, we can know that the sum:
1 − 2 + 3 + 4 − 5 + 6 + … + 1 9 9 9 − 2 0 0 0 + 2 0 0 1
is actually the sum of the arithmetic progression:
2 + 5 + 8 + … + 2 0 0 0
with a = 2 , d = 3 and T n = 2 0 0 0
Use the formula to find the value of n :
T n = a + ( n − 1 ) ( d ) 2 0 0 0 = 2 + ( n − 1 ) ( 3 ) ⟹ n = 6 6 7
Make use of the formula S n = 2 n ( a + T n ) to find the value of the expression:
1 − 2 + 3 + 4 − 5 + 6 + … + 1 9 9 9 − 2 0 0 0 + 2 0 0 1 + 2 0 0 2 − 2 0 0 3 = ( 2 + 5 + 8 + … + 2 0 0 0 ) + ( 2 0 0 2 − 2 0 0 3 ) = 2 6 6 7 ( 2 + 2 0 0 0 ) − 1 = ( 6 6 7 ) ( 1 0 0 1 ) − 1 = 6 6 7 6 6 7 − 1 = 6 6 7 6 6 6
Problem Loading...
Note Loading...
Set Loading...
For every 3 terms, there would be the following combination:
1-2 ... +3
4-5 ... +6
7-8 ... +9 and so on...
2001÷3=667
The whole expression will become:
-1(667)+(3×1+3×2+3×3+3×4+...+3×667)+2002-2003
=-677+3[ 2 6 6 7 ( 6 6 8 ) ]+(-1)
= 6 6 7 6 6 6